2015
DOI: 10.1515/dx-2014-0058
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and impact of a clinical diagnostic decision support tool at an academic medical center

Abstract: Background: Use of differential diagnosis (DDX) generators may reduce the incidence of misdiagnosis-related harm, but there is a paucity of research examining the use and impact of such systems in real-world settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
(12 reference statements)
0
5
1
1
Order By: Relevance
“…10 This 2013 pilot study by Henderson and Rubin 10 looked at the utility of the Isabel DDx Generator in general practice and found that the system was not likely to be used in its current format in primary care. Even when systems were well adopted in clinical practice, such as in the study by Barbieri et al 9 of VisualDX ’s uptake in an acute setting, it is not clear how the system affects the clinician and patient who are involved in its use. This study is therefore unique and can inform future work on decision making diagnostic software.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 This 2013 pilot study by Henderson and Rubin 10 looked at the utility of the Isabel DDx Generator in general practice and found that the system was not likely to be used in its current format in primary care. Even when systems were well adopted in clinical practice, such as in the study by Barbieri et al 9 of VisualDX ’s uptake in an acute setting, it is not clear how the system affects the clinician and patient who are involved in its use. This study is therefore unique and can inform future work on decision making diagnostic software.…”
Section: Discussionmentioning
confidence: 99%
“…An unpublished literature review and market-research activity, which took place alongside this project, found that there were only a small number of systems that met this description 7 and were commercially available, 8 and that some of the newer systems only had a small amount of published research regarding them. 9 While the systems did appear to have the potential to improve diagnostic practices in clinicians, 7 it was not entirely clear that they were being used effectively when trialed in clinical practice. 9,10 There was also a concerning lack of evidence surrounding patient-facing symptom checkers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, three other intervention studies found that use of a CET did not reduce referrals to dermatology [ 13 , 32 , 33 ]. While reduction of referrals and other return appointments may be a clinical goal to save patient and provider time and to reduce costs, its attainment through usage of CETs has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…В этих условиях одним из перспективных направлений повышения качества медицинской помощи больным дерматовенерологического профиля, отвечающих современным требованиям, является создание интеллектуальных информационно-диагностических и обучающих систем поддержки принятия решений, а также развитие на их базе телемедицинских технологий [5][6][7][8][9][10][11][12]. Системы дистанционного обучения нередко бывают одним из компонентов интеллектуальных систем поддержки принятия решений, а результаты их практического использования свидетельствуют об их более высокой эффективности в сравнении с традиционными образовательными подходами [13][14][15].…”
unclassified